Biological synthesis of zinc nanoparticles by aspergillus niger - Noorbatcha, Ibrahim Ali; Mohd. Salleh, Hamzah (Journal of Pure and Applied Microbiology, 2014)
Nanoparticles have gained interest due to its unique properties and benefits that can upgrade the future technologies. However, the production of nanoparticles has adopted physical and chemical methods which have been proven as non-eco friendly and produces toxic products. The present study proposes an eco-friendly synthesis of zinc nanoparticles using a wide range of microorganisms. The synthesis of Zinc nanoparticles using Aspergillus niger, and the effect of the biomass ratio to the salt solution and effect of different type of salt solution are presented in this paper. The fungus is grown in a suitable medium and biomass was taken (varies) to be challenged with the zinc sulphate salt solutions and zinc nitrate salt solution (at different concentration) for 72 hours. The formations of nanoparticles were characterized using UV–Vis spectrophotometer and Scanning Electron Microscope (SEM) to ascertain the size and polydispersity of the nanoparticles produced. The synthesis shows that lower ratio of biomass used in the synthesis give faster indication of nanoparticle formation and tolerance of the fungi mycelia different to the different concentration and type of the salt solutions.